Dynamics Behavior Analysis of Parallel Mechanism with Joint Clearance and Flexible Links - Chen Xiulong; Jia Yonghao; Deng Yu; Wang Qing (Shock and Vibration)
In this study, the dynamics behaviors analysis of parallel mechanism considering joint clearance and flexible links are investigated using a computational methodology. The nonlinear dynamic model of 4-UPS-RPS spatial parallel mechanism with clearance in spherical joint and flexible links is established by combining KED method and Lagrange method. The dynamic responses including collision force and motion characteristics of the moving platform are obtained. Chaos and bifurcation are analyzed. The effects of different clearances on the dynamics behaviors of the parallel mechanism are studied. The results show that 4-UPS-RPS spatial parallel mechanism is very sensitive to joint clearance and flexible links, and small variations in the clearance value can cause the mechanism change from periodic motion to chaotic motion. This research provides a methodology for forecasting the dynamics behavior of parallel mechanisms with clearance and flexible links.